Мелкоразмерные твердосплавные спиральные сверла с переменным углом наклона стружечных канавок - Турманидзе, Р. С.; Кушнаренко, О. Н.; Адамия, Д. Р.; Гвиниашвили, З. М. (НТУ "ХПИ", 2010)
В статье проанализировано влияние угла наклона стружечных канавок на прочность и стойкость мелкоразмерных твердосплавных сверл. В серии экспериментов сверла с переменным углом показаны более высокие показатели износостойкости при обработке материала для печатных плат.

In the submitted work are shown the analysis of influence of the setting angle of chip grooves on strength and durability of fine-sized spiral drills and the basing of the utilization effectiveness of spiral drills with variable angle in comparison with standard drills. Also are given the results of preliminary experiments and the work plan of subsequent investigations.
Keywords: прочность; износостойкость; обработка механическая